Proposed Marketing Strategy for Freight Services Based on Consumer Preferences and Perceptions with the Multidimensional Scaling Method - DELFI MAIROZA (JTI: Jurnal Teknik Industri, 2020)
This research is one of the freight forwarding companies in Indonesia to various regions or cities. However, the presence of many freight forwarding companies has caused many competitors to make it less a priority for SMEs to deliver goods. The purpose of this study is to design a marketing strategy for freight forwarding services based on consumer preferences and perceptions. The method used in this research is Multidimensional Scaling. This method is one procedure for classifying consumer preferences and perceptions based on visual similarities in a geometry. The results of this study are in the form of a proposed marketing strategy for freight forwarding services based on the 7P (Marketing Mix) mix concept.